2022
DOI: 10.1021/acs.jchemed.2c00171
|View full text |Cite
|
Sign up to set email alerts
|

Student Perceptions of Learning in Biochemistry Using a Science Communication Focused Writing Assignment

Abstract: With the highly interdisciplinary nature of biochemistry, and the diverse range of students taking introductory biochemistry courses, it can be difficult to incorporate authentic applications of course content that appeal broadly to students. However, it is important to engage students‘ learning at the affective level. One mode to achieve this goal is by incorporating assignments that support students in identifying the relevance of course content and the skills they are learning. In this study we incorporated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(15 citation statements)
references
References 38 publications
2
13
0
Order By: Relevance
“…Both quantitative course evaluation results and qualitative student comments indicated that the short course positively influenced students’ perceptions of chemistry learning relevance from individual, societal, and vocational perspectives. This finding aligns with previous research, suggesting that selecting student-interest topics supports the individual perspective of relevance. , Introducing real-life application examples addresses societal and vocational relevance dimensions, while also strengthening knowledge related to potential careers. Moreover, the students’ responses to survey questionnaires revealed positive changes in students’ motivation levels after implementing the instructional unit.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…Both quantitative course evaluation results and qualitative student comments indicated that the short course positively influenced students’ perceptions of chemistry learning relevance from individual, societal, and vocational perspectives. This finding aligns with previous research, suggesting that selecting student-interest topics supports the individual perspective of relevance. , Introducing real-life application examples addresses societal and vocational relevance dimensions, while also strengthening knowledge related to potential careers. Moreover, the students’ responses to survey questionnaires revealed positive changes in students’ motivation levels after implementing the instructional unit.…”
Section: Discussionsupporting
confidence: 89%
“…Feedback highlighted the course's success in contextualizing academic content within practical applications, thereby enhancing perceived learning benefits. 9 Vocational Dimension Perceptions. Notably, 91.2% of respondents felt that they had gained crucial knowledge for their This finding is in line with prior research studies, 7,8 which suggested that the enhanced perception of chemistry learning relevance in students may be primarily attributed to course content, rather than changes in pedagogy.…”
Section: Assessment Of Chemistry Learning Relevancementioning
confidence: 99%
See 2 more Smart Citations
“…Recently, there has been information in the literature regarding diversity, inclusion, access, and equity in the chemistry curriculum. The subject of cultural relevance and creating personal connections for students within the chemistry classroom is also a matter of discussion in the literature. The list of scientists currently used for the Scientist Report assignment includes names historically mentioned during a typical general chemistry course. Additional names are being investigated for inclusion in order to create a more diverse list.…”
Section: Scientist Report Assignmentmentioning
confidence: 99%